A 2020 vision for food, agriculture and the environment in Latin America: a synthesis - Garrett, James L. (International Food Policy Research Institute, 1995)
In this synthesis, specific goals and strategies are outlined. The nations of Latin America can achieve the following goals for food, agriculture, and the environment by the year 2020. Although other regions will certainly share these goals, the sweeping changes now occurring in Latin America present the region with the opportunity to pursue novel strategies to achieve the vision. Specific goals and strategies consonant with the present and future reality of Latin America are developed below for four areas: poverty, food security and nutrition, agriculture and natural resources, and the political and institutional environment.